The Impact of Constitutional Court Decision Number 84/PUU-XXII/2024 on the Retirement Age Limit for Notaries from the Perspective of Justice and Legal Certainty - Meidya Utama Prayoga; Agus Riewanto; Nugraheni, Anjar Sri Ciptorukmi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Constitutional Court Decision Number 84/PUU-XXII/2024 introduces significant changes to the regulation of the retirement age for notaries in Indonesia. Previously, the Notary Position Law strictly limited the retirement age to 65 years, or up to 67 years with an extension. However, through this decision, the Court allows notaries to remain in office beyond the age of 67, provided they meet physical and mental health requirements as well as demonstrate professional integrity. This study employs a normative legal research method with a descriptive approach, using both doctrinal analysis and primary and secondary data sources. The findings reveal that the decision has amended the retirement age limit for notaries from 67 to 70 years. Furthermore, it provides an opportunity for notaries to serve beyond that age as long as they meet the health criteria. From a justice perspective, this is seen as a protection of constitutional rights; however, it still requires clear and objective parameters to avoid inequality. While the extension acknowledges the competence of senior notaries, it may hinder generational renewal and create legal uncertainty without proper oversight. Therefore, the role of professional organizations and the government is essential to ensure fair and professional implementation.